The prevalent of tobacco use Among health workers in Juba Teaching Hospital - Cham, Akway M.; De Awar, Gai Mabil; Mayen Buk, Madut; John, Chol Deng; Ngor, David Alew; Odong, Patrick; Samuel, Albert Juma (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Smoking continues to be a public health threat despite the progress that has been made. Health care staff should lead the fight in term of educating public about health hazard of tobacco and advising people to quit smoking. The objective of this study is to understand the epidemiology of smoking among Juba Teaching Hospital health workers in Juba city South Sudan Methodology: A cross-sectional study using semi- structured questionnaires administered to a selected sample of respondents at Juba Teaching Hospital (JTH). Participants were asked about demographics, activities, reason for smoking and attitude toward smoking. Results: From the 171 respondents (with response rate of 85.5%) smoking prevalence was 23.39%. The majority of respondents were male 60% while the remaining percentages were female (40%). The prevalence was highest in males compared to females. Age specific percentage of smoking was highest in the age group 26–35 years. Motive for smoking include: Concentration, Peer pressure, relaxation and stress release were the major factors mentioned by participants.